Analisis Pengukuran Kinerja Koperasi Tani Duta Kartika Kencana dengan Pendekatan Balanced Scorecard - Kusuma, I Gede Candra; Suryanawa, I Ketut (E-Jurnal Akuntansi, 2021)
Balanced scorecard research is based on various theories and backgrounds in different places. The research was conducted at the Duta Kartika Kencana Farmer's Cooperative, which still performs traditional measurements, which only looks at the financial aspect so that it is not in accordance with the targets to be achieved by the cooperative. Performance measurement based on the balanced scorecard is the goal of this research, especially at the Duta Kartika Kencana Farmers Cooperative. This type of research is a case study. Descriptive and comparative analysis are data analysis techniques. Finance, customers, internal business processes as well as learning and growth into a balanced scorecard perspective. Based on the results of the measurement analysis that has been carried out, it shows that the performance of the Duta Kartika Kencana Farmers Cooperative as a whole is quite good, this is shown from the scores generated by each perspective. Keywords : Balanced Scorecard; Cooperative; Performance Appraisal.